The role of NOD-like receptors in innate immunity - Almeida-da-Silva, Cássio Luiz Coutinho; Savio, Luiz Eduardo Baggio; Coutinho-Silva, Robson; Ojcius, David M. (Frontiers in Immunology, 2023)
The innate immune system in vertebrates and invertebrates relies on conserved receptors and ligands, and pathways that can rapidly initiate the host response against microbial infection and other sources of stress and danger. Research into the family of Nod-like receptors (NLRs) has blossomed over the past two decades, with much being learned about the ligands and conditions that stimulate the NLRs and the outcomes of NLR activation in cells and animals. The NLRs play key roles in diverse functions, ranging from transcription of MHC molecules to initiation of inflammation. Some NLRs are activated directly by their ligands, while other ligands may have indirect effects on the NLRs. New findings in coming years will undoubtedly shed more light on molecular details involved in NLR activation, as well as the physiological and immunological outcomes of NLR ligation.